Academician N. М. Аmоsоv was born 100 years ago - Knyshov, Gennadiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The article deals with 100 years after the birth of an outstanding cardiosurgeon, scientist-experimentalist, philosopher, writer, public figure, popularizer of science and healthy life-style Amosov N. M.